Community Participation in Conservation and Development: A Case of Sikles Village in Annapurna Region - Gurung, Shibaji (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Conservation of nature and biodiversity, together with livelihood maintenance and socioeconomic advancement of the local community, has always been a contested issue. This paper attempts to analyze the nature and extent of community participation in the conservation and development programs in Sikles Village of the Annapurna Conservation Area Project (ACAP) region and assess role of such community participation in the livelihood of the local people. The research used a mixed method. The primary data were collected through a household survey and interviews. The samples were selected from five clusters of Sikles Village. In total, 83 households were chosen as samples for the survey. In addition, interviews were also taken with selected representatives of the Conservation Area Management Committee (CAMC) and villagers. The conservation and development programs launched by ACAP in Sikles Village are carried out with the participation of the local people. The CAMC facilitates the process of community participation and it is compatible with the indigenous practices of the local community. However, the participation of the community is mostly at the implementation stage. The research shows that the decisive role is still limited to the village elites present in the CAMC and the experts of ACAP. Moreover, the formation of CAMC is exclusionary from caste/ethnicity and gender perspective. The people whose livelihood strategies are agriculture and animal husbandry are benefited from the conservation initiatives of ACAP.